1994
DOI: 10.1111/j.1527-2001.1994.tb00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothering, Diversity, and Peace Politics

Abstract: The most popular uniting theme in feminist peace literature grounds women's peace work in mothen'ng. I argue if maternal arguments do not address the variety of relationships different races and classes of mothers have to institutional violence and/or the military, then the resulting peace politics can only draw incomplete conclusions about the relationships between maternal worklthinking and peace. To illustrate this I compare two models of mothering: Sara Ruddick's decription of "maternal practice" and Patri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 5 publications
0
24
0
1
Order By: Relevance
“…However, literature on Ruddick's work has suggested that despite her practicalist approach, her construction of a broad, universalistic account of mothering tethers her framework of mothering to a white, middle‐class perspective in a way that may also lead to suspicion about its promises for trans and gender‐creative youth. For example, Alison Bailey critiques Ruddick's universalization of maternal practice into the categories of preservative love, nurturance, and training as a totalizing, ethnocentric move (Bailey , 192). Bailey argues that Ruddick's epistemic framework of mothering relies on the sameness provided by universal categories, and instead turns to an emphasis on mothering as a field of difference (192–93).…”
Section: Where Is Trans Care Ethics? Trans Dependency and Feminismmentioning
confidence: 99%
See 2 more Smart Citations
“…However, literature on Ruddick's work has suggested that despite her practicalist approach, her construction of a broad, universalistic account of mothering tethers her framework of mothering to a white, middle‐class perspective in a way that may also lead to suspicion about its promises for trans and gender‐creative youth. For example, Alison Bailey critiques Ruddick's universalization of maternal practice into the categories of preservative love, nurturance, and training as a totalizing, ethnocentric move (Bailey , 192). Bailey argues that Ruddick's epistemic framework of mothering relies on the sameness provided by universal categories, and instead turns to an emphasis on mothering as a field of difference (192–93).…”
Section: Where Is Trans Care Ethics? Trans Dependency and Feminismmentioning
confidence: 99%
“…Whereas Bailey powerfully stresses that a difference approach to mothering is the only way to not cede epistemic priority to white, middle‐class visions of maternal practices (Bailey , 195), Keller stresses a “middle path” between “Ruddick's universalism and localized accounts of mothering,” with a focus on encouraging more voices to join the discussion of mothering while holding onto Ruddick's useful work of categorization (Keller , 844). Interestingly, Keller also specifically mentions mothering gender‐nonconforming youth in this context (845–46, 848–49).…”
Section: Where Is Trans Care Ethics? Trans Dependency and Feminismmentioning
confidence: 99%
See 1 more Smart Citation
“…Collins () called this motherwork , which is defined as a differentiated set of communal mothering activities “of survival, identity, and empowerment that form the bedrock of women of color's mothering” (p. 7). As Bailey () noted, “Collins's motherwork is structured by racial‐ethnic mothers’ struggle over the definition and control of their caring labor, to empower themselves so that they may meet and manage the needs of their own children and their communities” (p. 194). How can we capture this dynamic of motherwork in a way that is recognized as an asset to the leadership competencies of African American women?…”
Section: Narratives Of Women and Workmentioning
confidence: 99%
“…Dietz argues that maternal thinking "distorts the meaning of politics and political action largely by reinforcing a onedimensional view of women as creatures of the family" (1985,20). Furthermore, several scholars have pointed out that theories which rely on the idea of 'mother' are often ethnocentric and, like the western-centrism present in Chodorow and Gilligan's works, cannot be universalized to all women (Bailey 1994(Bailey , 1995Collins 1994;DiQuinzio 1993; for an overview see Keller 2010 (1989,133) By using standpoint theory, Ruddick sees maternal practice as work that "has been performed by women and has created 'women' as they are" (emphasis added, 1989, 133). She does not imply that maternal thinking is a natural part of 'being' a woman.…”
Section: First Generation Care Ethicsmentioning
confidence: 99%